Sudan's Market Share in Saudi Live Sheep Imports: Situation Analysis and Trend1 (University of Khartoum Journal of Agricultural Sciences, 2023)
: High demand for live sheep in the Saudi market resulted intough competition among the exporting countries including Sudan. Theobjective of this paper was to estimate the Sudan export market share(EMS) against its main competitors in the Saudi live sheep import market.Published secondary data, from Sudan, Kingdom of Saudi Arabia (KSA)and other related sources were obtained for the period 1992-2013. Trendanalysis and EMS index were applied to achieve the paper objectives. Theresults revealed that the annual average import capacity of the Saudimarket for live sheep, during the study period, was about 163000 tons.Sudan's EMS was about 30%. It ranked first followed by Syria, Australiaand Somalia. Generally, there was no stable live sheep exportperformance. Trends of volumes and earnings of live sheep exported toKSA reflected frequent fluctuations for most of the exporting countriesincluding Sudan. Based on the findings, the paper recommends moreofficial support to be directed towards this export business. Export policyreform is a necessary action towards strengthening Sudan's position as amajor exporter of live sheep to Saudi Arabia given the many Sudaneseexport sheep advantages such as superior quality, vicinity to the Saudimarket, adaptation to the Saudi environment, abundance of productionand the historic, economic and social relations between the two countries.Also of importance, is embarking on a comprehensive promotion effortfor this commodity through all possible means. Moreover, conscious work
Keywords: Live sheep; Sudan exports; Saudi market; trend; market share; competition